Barriers and enablers to make lifestyle changes among type 2 diabetes patients: a review - Mohamed Nor, Noraishah; Mohd Shukri, Nor Azwani; Sidek, Suriati; Azahari, Nuraniza (UKM Press, 2019)
Type 2 diabetes is a non-communicable disease that affects most people around the world and is generally the result of excessive food intake and physical inactivity. Therefore, the purpose of this review was to identify facilitators and barriers for lifestyle modifications among type 2 diabetes patients. We combined quantitative and qualitative studies for this systematic narrative review. A literary search was carried out using EBSCO, HighWire Press, Medline, PsycInfo, PubMed and Scopus. Narrative review was used to extract results from quantitative studies, while thematic synthesis was used to extract results from qualitative studies. Twenty-three studies were included in this review, with a total of 2287 participants from Western, Arab and Asian populations. The two main themes generated from this review are intrinsic factors and extrinsic factors that can either be facilitators or barriers to implementing lifestyle change. Among the barriers faced by the participants are established food habits, lack of self-efficacy, lack of motivation, lack of social support, inadequate knowledge, low socio-economic status, food culture and poor time management. In contrast, the facilitating factors generated are strong self-efficacy, high motivation, good habits, and sufficient knowledge. In general, patients with diabetes observed more barriers than facilitators to implementing healthy lifestyle changes.